Generation of ϵ, ϵ‐Difluorinated Metal‐Pentadienyl Species through Lanthanide‐Mediated C−F Activation. Issue 65 (9th November 2017) - Kumar, Tarun; Massicot, Fabien; Harakat, Dominique; Chevreux, Sylviane; Martinez, Agathe; Bordolinska, Klaudia; Preethalayam, Preethanuj; Kokkuvayil Vasu, Radhakrishnan; Behr, Jean‐Bernard; Vasse, Jean‐Luc; Jaroschik, Florian
Abstract: Heavy metal on Lewis acid : The combination of lanthanide metals and AlCl3 has been employed for selective single C−F activation in benzofulvenes comprising an exocyclic CF3 substituent. Intermediate ϵ, ϵ‐difluorinated metal‐dienyl species react with a large variety of aldehydes in a highly regio‐ and diastereoselective fashion to afford 1, 1‐disubstituted indenes bearing a difluorovinyl group. These new building blocks have been further transformed through a hydrogenation–cyclization process into fluorinated heterocyclic spiro compounds. Abstract : Heavy metal on Lewis acid : Lanthanides and AlCl3 have been employed for selective single C−F activation in benzofulvenes. Intermediate ϵ, ϵ‐difluorinated metal‐dienyl species react with a large variety of aldehydes in a highly regio‐ and diastereoselective fashion to afford 1, 1‐disubstituted indenes bearing a difluorovinyl group. These new building blocks have been further transformed through a hydrogenation–cyclization process into fluorinated heterocyclic spiro compounds.